2016
DOI: 10.1080/09553002.2016.1207821
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of miRNAs in mouse thymus responses to ionizing radiation by deep sequencing

Abstract: To investigate the potential regulatory roles of microRNA (miRNA) in mouse response to ionizing radiation (IR)-induced thymus injury, miRNA expression profiles of mouse thymus with or without IR were analyzed using deep sequencing technology. Potential target candidates of the identified miRNA were predicted using RNAhybrid and miRanda. Differently expressed miRNA targets functional annotation and pathways were noted using Swiss-Prot, Gene Ontology (GO), Clusters of Orthologous Groups (COG), Kyoto Encyclopedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In the radiation injury model, the expression of miR‐147 and PI3K/AKT was the opposite. MiR‐147 significantly increased after radiation, but the PI3K/AKT signaling pathway was inhibited. MiR‐147 inhibits the PI3K/AKT/mTOR signaling pathway to prevented proliferation and migration of breast cancer cells, but its direct target was not elucidated .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the radiation injury model, the expression of miR‐147 and PI3K/AKT was the opposite. MiR‐147 significantly increased after radiation, but the PI3K/AKT signaling pathway was inhibited. MiR‐147 inhibits the PI3K/AKT/mTOR signaling pathway to prevented proliferation and migration of breast cancer cells, but its direct target was not elucidated .…”
Section: Discussionmentioning
confidence: 97%
“…In PDPK1 gene knockout cells or mice, AKT kinases were inactivated, indicating that PDPK1 was an important upstream kinase of AKT, and the loss of AKT activity was related to restriction of phosphorylation of itself . MiR‐147 significantly increased after radiation, but the PI3K/AKT signaling pathway was inhibited . MiR‐147 inhibits the PI3K/AKT/mTOR signaling pathway to prevented proliferation and migration of breast cancer cells, but its direct target was not elucidated …”
Section: Introductionmentioning
confidence: 99%
“…miR-147 was upregulated in the mouse thymus in response to ionizing radiation by deep sequencing analysis. 15 It was also found that up-regulation of miR-147 inhibited the expression of pro-inflammatory cytokines (such as TNF-α and IL-6), indicating that miR-147 exhibited potent anti-inflammatory properties and functions as a negative regulator of TLR/NF-κB-mediated pro-inflammatory cytokines. 32 In the radiation damage model, miR-147 and PI3K/PDPK1/AKT expression trends are exactly the opposite.…”
Section: Discussionmentioning
confidence: 98%
“… 32 In the radiation damage model, miR-147 and PI3K/PDPK1/AKT expression trends are exactly the opposite. It was observed that the level of miR-147 was significantly upregulated, 15 whereas activation of the PI3K/AKT signaling pathway was inhibited. 33 , 34 No study has analyzed miR-147 expression in response to radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation